Influence of depth of interaction upon the performance of scintillator detectors. - Mark S Brown; Stefan Gundacker; Alaric Taylor; Clemens Tummeltshammer; Etiennette Auffray; Paul Lecoq; Ioannis Papakonstantinou (PLoS ONE)
The uncertainty in time of particle detection within a scintillator detector, characterised by the coincidence time resolution (CTR), is explored with respect to the interaction position within the scintillator crystal itself. Electronic collimation between two scintillator detectors is utilised to determine the CTR with depth of interaction (DOI) for different materials, geometries and wrappings. Significantly, no relationship between the CTR and DOI is observed within experimental error. Confinement of the interaction position is seen to degrade the CTR in long scintillator crystals by 10%.